2011
DOI: 10.1262/jrd.10-023t
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Uterine Blood Flow, Peripheral Sex Steroids, Expression of Endometrial Estrogen Receptors and Nitric Oxide Synthases During the Estrous Cycle in Mares

Abstract: Abstract. The objective of this study was to investigate the relationships between uterine perfusion and estrogen, progesterone and the uterine nitric oxide synthase (NOS) system in five trotter mares during the estrous cycle. Color Doppler sonography for measurement of uterine blood flow and collection of blood for determination of plasma estrogen and progesterone concentrations were performed on days 0 (= ovulation), 1, 5, 11 and 15 and daily during estrus (days -1 to -4) of one estrous cycle; endometrial bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
0
17
1
Order By: Relevance
“…Previously, a positive correlation between endometrial transcripts of ESR1 and ESR2 were observed throughout the equine estrous cycle (Honnens et al, 2011). In addition, there were effects of estrous cycle day on the expression of ESR1 and ESR2 (Honnens et al, 2011).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Previously, a positive correlation between endometrial transcripts of ESR1 and ESR2 were observed throughout the equine estrous cycle (Honnens et al, 2011). In addition, there were effects of estrous cycle day on the expression of ESR1 and ESR2 (Honnens et al, 2011).…”
Section: Discussionmentioning
confidence: 87%
“…Previously, a positive correlation between endometrial transcripts of ESR1 and ESR2 were observed throughout the equine estrous cycle (Honnens et al, 2011). In addition, there were effects of estrous cycle day on the expression of ESR1 and ESR2 (Honnens et al, 2011). Since we compared ESR2 during the preovulatory period, late diestrus and early pregnancy in postmortem specimens, and did not evaluate its expression at other time points of the estrous cycle, we could therefore have missed differences in ESR2 mRNA expression across different days of the reproductive cycle.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In fact, in the mare endometrium, during estrus, high levels of ovarian steroid receptors, such as ER , ER and PR mRNA and protein have been detected in luminal and glandular epithelia, as well as in stromal cells (Watson et al 1992, Gebhardt et al 2012, Silva et al 2014. In addition, a positive correlation between mRNA expression of ER and ER has been reported in mare endometrium (Honnens et al 2011). In the luteal phase, when circulating P4 levels are high, endometrium expression of ER and PR are inhibited.…”
Section: Introductionmentioning
confidence: 99%
“…In mares, NO seems to be implicated in both in follicular growth and ovulation (Pinto et al, 2002) and is also a potential mediator of luteal development and maintenance, angiogenesis, and blood flow (Ferreira et al, 2011). Also, Honnens et al, (2011) found that NO regulates uterine blood flow during the estrous cycle in mares. Therefore, the present study aimed to evaluate ovarian changes and its relation to oxidative stress during early postpartum period in Arabian horses.…”
Section: Introductionmentioning
confidence: 99%